INNOVATION OF LEARNING MEDIA THROUGH INFORMATION AND COMMUNICATION TECHNOLOGY IN THE REVOLUTION ERA 4.0 - Maria Ulfa; Ine Rahayu Purnamaningsih (PROJECT (Professional Journal of English Education), 2022)
The existence of globalization has made a shift in the times, starting from the era of writing, printing, to bringing about this period, namely the Revolution Era 4.0. This has led to Information and Communication Technology is growing rapidly at this time, and humans are required to keep up with the times, including in the field of education. The method used in this research is a literature study, which is carried out in stages in the form of searching, finding relevant data, and expressing ideas from the findings. Based on the research results, teachers have challenges to master the skills of using technology. In today's learning, innovation is needed in choosing learning media. Teachers must be creative and innovative in choosing learning media. Learning media that can be used in this era are computers, youtube, and and other media such as WhatsApp, telegram, and e-mail. It aims to make learning efficient, effective and interesting. Keywords:  Learning Media, Information and Communication Technology, Revolution Era 4.0.